2018
DOI: 10.1353/hpu.2018.0080
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Mediates Racial Disparities in Cardiopulmonary Resuscitation Knowledge among Chronic Kidney Disease Patients

Abstract: Black patients with chronic kidney disease (CKD) receive more cardiopulmonary resuscitation (CPR) than other racial groups, and knowledge of CPR influences preferences for care. As limited health literacy disproportionately affects Blacks and contributes to disparities in end-of-life (EOL) care, we investigated whether health literacy mediates racial disparities in CPR knowledge. Black and White adult patients with advanced CKD completed CPR knowledge surveys. Health literacy was assessed using the Rapid Estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
(38 reference statements)
0
21
0
Order By: Relevance
“… 25 Lower rates of patient activation (ie, confidence to engage in health care and treatment decisions among marginalized patients) because of frequent and recurrent inequitable treatment by the health system may play a role in the demonstrated differences in paroxysmal AF management. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“… 25 Lower rates of patient activation (ie, confidence to engage in health care and treatment decisions among marginalized patients) because of frequent and recurrent inequitable treatment by the health system may play a role in the demonstrated differences in paroxysmal AF management. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…LHL was associated with worse control of blood pressure [ 55 , 61 ], lower medication adherence confidence [ 44 , 53 ] and lower quality of life [ 56 ]. For worse treatment and self-care knowledge [ 7 , 41–43 , 49 , 52 , 53 , 79 ], worse self-care behaviours [ 7 , 40 , 43 , 51 , 55 ], including lifestyle [ 40 , 50 , 51 ] and adherence problems [ 8 , 38 , 46 , 51 , 53 ] some studies found an association with LHL, while others did not. LHL was not associated with CKD awareness [ 33 , 47 ], treatment preferences [ 67 ], disaster preparedness [ 57 ] and phosphate regulation [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…A potential explanation for our weak evidence could lie in our separate assessment of various mediating factors, instead of lumping them together. For example, we found separate associations of LHL with knowledge of medication [ 44 , 46 ], lifestyle [ 7 ], disease [ 42 ], transplant [ 44 , 49 ] and cardiopulmonary resuscitation [ 52 ]. We think that these factors are too heterogeneous to combine validly.…”
Section: Discussionmentioning
confidence: 99%
“…This compared with a 46% and 22% higher risk of death and DNR utilization, respectively, among other race/ethnicities. Although lower DNR utilization might reflect less advance care planning among Black patients, [16][17][18][19][20] including those with kidney disease, 21,22 we have also recently used the same Philips Healthcare data set to demonstrate racial disparities in critical care access. 23 Accordingly, the effect of prehospital practices, such as primary care 24,25 and health literacy, 26 versus the effect of within hospital practices, such as the counseling of admitting physicians, on resuscitation orders is uncertain.…”
Section: Discussionmentioning
confidence: 99%